2015
DOI: 10.1186/s12905-015-0260-8
|View full text |Cite
|
Sign up to set email alerts
|

The HysNiche trial: hysteroscopic resection of uterine caesarean scar defect (niche) in patients with abnormal bleeding, a randomised controlled trial

Abstract: BackgroundA caesarean section (CS) can cause a defect or disruption of the myometrium at the site of the uterine scar, called a niche. In recent years, an association between a niche and postmenstrual spotting after a CS has been demonstrated. Hysteroscopic resection of these niches is thought to reduce spotting and menstrual pain. However, there are no randomised trials assessing the effectiveness of a hysteroscopic niche resection.Methods/DesignWe planned a multicentre randomised trial comparing hysteroscopi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
69
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(74 citation statements)
references
References 34 publications
0
69
0
5
Order By: Relevance
“…However, because suture is not possible with hysteroscopy, CSD would be enlarged and the myometrial thickness at the level of the uterine isthmus would be further decreased. Also, this treatment has a risk of bladder injury and uterine perforation while applying thermal energy to the scar. Furthermore, this technique could increase the risk of uterine rupture during a subsequent pregnancy, and recurrences are still possible in the long term.…”
Section: Discussionmentioning
confidence: 99%
“…However, because suture is not possible with hysteroscopy, CSD would be enlarged and the myometrial thickness at the level of the uterine isthmus would be further decreased. Also, this treatment has a risk of bladder injury and uterine perforation while applying thermal energy to the scar. Furthermore, this technique could increase the risk of uterine rupture during a subsequent pregnancy, and recurrences are still possible in the long term.…”
Section: Discussionmentioning
confidence: 99%
“…The lower rim of the niche, if prominently visible, was resected as described by Chang et al and Fabres et al14, 17 The niche surface was superficially coagulated with the use of a rollerball (Figures 1 and S2). 24 …”
Section: Methodsmentioning
confidence: 99%
“…Three months after randomisation niche depth and residual myometrium were measured by transvaginal sonography according to a standardised method 24. Women were offered to undergo sonohysterography; however, this was omitted if women refused.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For patients with CSD presenting with postmenstrual spotting and pain, hysteroscopic resection of the CSD niche at the time of hysteroscopic evaluation may result in alleviation of symptoms. Vervoort et al, reported a multicentre randomised trial (Dutch Trial NTR3269 -registered in February 2012) that might provide evidence on the cost effectiveness of hysteroscopic resection versus expectant management for symptomatic patients [10]. A conclusion drawn on the cost effectiveness analysis is expected to be available to guide the management of symptomatic patients who have no desire for pregnancy by the end of the trial.…”
Section: Discussionmentioning
confidence: 99%